DEVALUATION OF THE FEMALE CONDITION IN CONTEMPORARY: THE STEREOTYPE OF THE “NEW” WOMAN - Santos Pereira, Cristiane; de Jesus Nascimento, Valquíria (Revista Gênero e Interdisciplinaridade, 2022)
This work presents a discussion about the devaluation of the female condition in contemporary society, as a consequence of the maintenance of ideologies that continue to affirm the subordination of the feminine to the masculine. Based on a literature review, based on the phenomenon of gender inequality, the article proposes to analyze the historical conditions and the different socio-cultural determinations that influence the construction and maintenance of such a process. Important achievements made by feminist movements over time are presented, their repercussions in the historical struggle for gender equality, and questions are raised about the paradoxical affirmation of the “new” identity of women in the contemporary world, based on libertarian ideals, while it remains based on stereotyped patterns that delimit women’s identity formation.